(6p^2 + 2p) - (8p^2 - 3p)

Question

Asked 6/2/2013 8:52:00 PM

Updated 1/24/2016 11:45:40 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by Andrew. [1/24/2016 11:45:09 AM]

s

andrewpallarca|Points 22246|

Question

Asked 6/2/2013 8:52:00 PM

Updated 1/24/2016 11:45:40 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by Andrew. [1/24/2016 11:45:09 AM]

Rating

3

(6p^2 + 2p) - (8p^2 - 3p)

= (6p^2 + 2p) + (-8p^2 + 3p)

= -2p^2 + 5p

= (6p^2 + 2p) + (-8p^2 + 3p)

= -2p^2 + 5p

Added 1/24/2016 11:45:10 AM

This answer has been confirmed as correct and helpful.

3

(5p^2 + 8)+ (-8p^2 + 3)

= -3p^2 + 11

= -3p^2 + 11

Added 1/24/2016 11:45:40 AM

This answer has been confirmed as correct and helpful.

5 + 12r - 3r + 6
User: -3(-w +8)

Question

Updated 9/27/2015 1:31:24 PM

2 Answers/Comments

5 + 12r - 3r + 6

= (12r - 3r) + (5 + 6)

= 9r + 11

= (12r - 3r) + (5 + 6)

= 9r + 11

Added 7/4/2014 8:39:54 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/4/2014 3:52:38 PM]

Simplify the polynomial. 5g + 8k - 10g -2k
**Weegy:** -5g + 6k (More)

Question

Expert Answered

Updated 6/3/2013 7:21:39 PM

3 Answers/Comments

5g + 8k - 10g -2k = -5g + 6k

Added 6/3/2013 9:04:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/8/2014 4:47:08 PM]

you need to answer in a complete way by restating the question, for more information please refer to

Added 6/3/2013 9:10:28 AM

5g + 8k - 10g -2k = -5g + 6k

Grouping the above and bring the RHS equation,

5g-10g-5g+8k-2k-6k = 0

-10g = 0

ie g = 0

Grouping the above and bring the RHS equation,

5g-10g-5g+8k-2k-6k = 0

-10g = 0

ie g = 0

Added 6/3/2013 7:21:39 PM

This answer has been flagged as incorrect.

Flagged by andrewpallarca [6/8/2014 4:47:15 PM]

24.3 = 3(2 + y) User: Solve for y.
8 - 3y + 6y = 9.5
**Weegy:** 3y - 4 =6y - 19
3y -6y = -19 +4
-3y=-15
y=-15/-3
y=5 **User:** Solve for y.
12.4 + 4y = 2y + 6.4
**Weegy:** y=-2 (More)

Question

Updated 9/27/2015 1:30:45 PM

3 Answers/Comments

24.3 = 3(2 + y)

24.3 = 6 + 3y

-3y = 6 - 24.3

-3y = -18.3

y = -18.3/-3

y = 6.1

24.3 = 6 + 3y

-3y = 6 - 24.3

-3y = -18.3

y = -18.3/-3

y = 6.1

Added 9/27/2015 1:27:45 PM

This answer has been confirmed as correct and helpful.

8 - 3y + 6y = 9.5

8 - 3y = 9.5

-3y = 9.5 - 8

-3y = 1.5

y = 1.5/-3

y = -0.5

8 - 3y = 9.5

-3y = 9.5 - 8

-3y = 1.5

y = 1.5/-3

y = -0.5

Added 9/27/2015 1:29:39 PM

This answer has been confirmed as correct and helpful.

12.4 + 4y = 2y + 6.4

4y - 2y = 6.4 - 12.4

2y = -6

y = -6/2

y = -3

4y - 2y = 6.4 - 12.4

2y = -6

y = -6/2

y = -3

Added 9/27/2015 1:30:45 PM

This answer has been confirmed as correct and helpful.

32,204,620

questions answered

There are no comments.